Interesting case of sudden unilateral blindness in a teenager: role of psychological intervention in psychogenic visual loss - Halawani, Motssim S. (International Journal of Advances in Medicine, 2019)
Visual loss complaints are commonly encountered by treating physicians, neurologist and ophthalmologists. More specifically a presentation of non-organic (psychogenic) blindness is less frequently seen but does exist and requires proper evaluation and specific skills for it to be properly managed. This case is of a 19 years old male who presented with acute monocular blindness post trauma whom he also had past psychiatric history. Post thorough assessment, no organic cause was identified, and a diagnosis of psychogenic blindness was made. Psychological therapy was beneficial in aiding return of his vision.